THE INFLUENCE OF WORK ENVIRONMENT AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Darmadi; N Lilis Suryani; Iman Syatoto (Asosiasi Dosen Muda Indonesia, 2024)
This research aims to determine how much positive and significant influence the work environment and work motivation have on the performance of Satpol PP employees and Subdistricts in the North Bambu City Region, West Jakarta, partially or simultaneously. The research method uses quantitative with a descriptive quantitative approach. The population used in this research were 80 employees of the Satpol PP and North Bambu City District, West Jakarta; the sample used was 60 employees. Data testing uses multiple linear regression tests. The research results show that the Work Environment variable partially and significantly affects the Employee Performance variable. The work motivation variable has a partial and significant effect on employee performance. Work Environment and Work Motivation variables simultaneously and significantly influence employee performance.